The expression of COX-2 and iNOS in ethanol and aspirin induced gastric ulcer rat models - sherly usman; Dewi Kartikawati Paramita; Yustina Andwi Ari Sumiwi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Aspirin or ethanol induced gastric ulcer rat models are the most frequently used in studies.Aspirin and ethanol induced gastric ulcers through different pathways involving COX-2 andiNOS. The aim of this study was to examine the expression of COX-2 and iNOS in gastriculcer rat model induced by ethanol and aspirin. Twenty-one Sprague Dawley rats weredivided into 7 groups i.e. control group (CA), ethanol 1st day (ED1), ethanol 3rd day (ED3),ethanol 5th day (ED5), aspirin 4th day (AD4), aspirin 6th day (AD6), and aspirin 8th day (AD8).Oral administration of aspirin was at 200mg/kgBW and the 100% ethanol at 1mL/200gBW.Macroscopic and microscopic observations were done to examine the gastric mucosaldamage, COX-2 and iNOS expressions. Severe gastric ulcers were observed in ED1and AD4 groups and mild gastric mucosal damage was observed in ED3, ED5, AD6 andAD8 groups. Microscopically, light erosion was shown by the CA and AD8 groups. Erosionwas also shown by ED3, ED5, and AD6 groups. The most severe damage with ulcers andheavier bleeding were shown by the ED1 and AD4 groups. Weak COX-2 expression wasfound in the CA, while the highest COX-2 expression was found in the ED1. The iNOSexpression in the ethanol groups was still increasing until the 5th day (ED5). In the aspiringroups, it reached the peak on the 3rd day (AD6), and already declined on the 5th day (AD8).In conclusion, the damage process of ethanol induced gastric ulcer occurred faster thanthat by aspirin. The highest COX-2 expression in the ethanol and aspirin groups wereshown at the onset begin. iNOS expression in ethanol induced ulcer groups still increaseduntil the 5th day, while in the aspirin induced ulcer groups already declined in the 5th day.